Research support from academic law libraries in the Western Cape in the scholarly legal research lifecycle - Moll, Elizabeth Margaret (Library and Information Studies Centre (LISC), 2022)
This study used an interpretive paradigm and a qualitative research approach to investigate the legal research lifecycle process used by legal academics at three institutions within the Western Cape, South Africa in order to ascertain academic law library research support services that would be able to support legal scholars using such a process. In order to do so, the researcher used four critical questions to guide the study which investigated the research lifecycle process used by legal scholars; existing and possible law library research support services discussed in the literature; current law library research support services in the Western Cape being offered to support legal scholars; and, the knowledge and skills required by law librarians to support legal research processes. A multiple case study method was used, with Stellenbosch University, the University of Cape Town and the University of the Western Cape as research sites. Purposive sampling of legal scholars and law librarians at three institutions was adopted. Data was gathered mainly through the administration of semistructured interviews with both the legal scholars and the law librarians, as well as via the literature for some aspects of the study. A conceptual framework, which used two conceptual models, namely, the research process lifecycle model and the Reference and User Services framework for LIS services, guided the theoretical aspect of the study. The researcher found that legal scholars favour the doctrinal approach to research, which still consists of the same stages involved in the research process model, but does not distinguish as clearly between the stages. A novel aspect of this study was the exploration of what constitutes legal data and it was found that it consists of literature, including cases and legislation. Law libraries should therefore be able to adapt their ‘data services' to this concept of legal data in order to better support legal scholars. A broad range of research support services were identified within the literature, but the study showed that law libraries in the Western Cape still rely on the ‘traditional' library services, for example, reference services and collection development. The study revealed that newer services, such as bibliometrics and research data services, could have applicability, although law librarians would need to adapt such services to the legal context. A disconnect between legal scholars and the law libraries that serviced them was seen in terms of awareness of library services, and therefore this study recommends that a targeted marketing approach as well as other relevant interventions be put in place in order to bridge this gap. Other recommendations include further study into how to ground new library research support services (such as research impact services or research data management services) in a legal context; as well as further study into the extent to which subject knowledge and/or a subject qualification is required to practice as a law librarian.